LiFePO4/C nano composite positive pole material and preparation method thereof - XU YUNLONG; MA HONGYAN; TAO LILI (2008)
The invention discloses a nano-composite positive material LiFePO4/C and a fabrication method, relating to a fabrication method of positive material of a lithium-ion battery. The invention uses the method of liquid-phase coprecipitation, the certain amount of lithium resource, iron resource and phosphate resource is weighted as the quality mol ratio of Li:Fe:P = (3.0-3.3):(1.0-1.1):(1.0-1.1), and the appropriate amount of carbon-doped material and organic surfactant is added in the reaction vessel; by controlling the reaction conditions like concentration, temperature etc. of the reaction solution, precursor gels are fabricated, and the precursor gels are separated, cleaned, filtered and dried to obtain precursor powder; the precursor powder is tableted and put into the crucible with microwave absorbent, and then the crucible is placed in the microwave oven, with the microwave power controlled between 100 to 600W and heated for 30 min, to obtain nano-sized composite positive material LiFePO4/C. The technique